Heterogeneity of the Effect of Affective Aspects on Students' Mathematical Problem-Solving Ability - Putri, Nadyati; Jupri, Al; Juandi, Dadang; Rachmi, Cut Nadia; Bulubaan, Santy (FKIP Universitas Lampung, 2025)
Mathematical Problem-Solving Ability (MPSA) is a crucial skill in mathematics learning, as it plays a role in understanding mathematical concepts and preparing students to face challenges in everyday life. This study aims to examine the heterogeneous influence of affective aspects such as self-efficacy (SE), self-regulated learning (SRL), self-concept (SC), and mathematical disposition (MD) on students' mathematical problem-solving ability (MPSA) through a systematic literature review. Data were collected from research articles published between 2019 and 2024, indexed in SINTA and Scopus, following the PRISMA guidelines. The analysis results indicate that SE has the strongest correlation with MPSA, followed by MD. Variability in SC highlights a context-dependent influence. This study also provides a comprehensive mapping related to publication years, sample sizes, educational levels, and research locations, showing trends in the variation of publications each year. These findings emphasize that educational interventions should integrate affective aspects of MPSA holistically, with strategies tailored to different educational levels and regional disparities. Therefore, recommendations for future research include developing more holistic learning strategies that integrate all four affective aspects to achieve better learning outcomes. Keywords: mathematical problem-solving ability, self-efficacy, self-regulated learning, self-concept, mathematical disposition, systematic literature review.